Estudio de la incidencia de la producción del cacao CCN-51 en el nivel de ingreso de los productores de la parroquia La Victoria, cantón Salitre, provincia del Guayas - Pepper Recalde, Marcos (2016)
Agriculture has been practiced since the dawn of humanity. Modifications have been made in agricultural areas over time; changes in terms of adaptation to natural factors as a function of economic and political systems. With the industrial revolution and the consequent need for increased food, agriculture, which until then had been traditional, it becomes progressively. The development of technology will play a very important role in the levels of productivity and diversification of agricultural products. Two types of approach to agriculture as a means of production is currently distinguished. Agriculture for a living, that is, more traditional conception .The agriculture as a way of living, that is, a point more economically. The modern history of Ecuador is characterized in its economic expression by the rise and the crisis in the export sectors. Traditionally the development of agro-exporting sectors has been a major factor in the dynamics of the Ecuadorian economy. At the time of its political independence, Ecuador is a mainly agricultural country………